Initiation of Social Financing for Poverty Alleviation Through Cash Waqf Linked Qurban (CWLQ) in Indonesia - Budiantoro, Risanda A.; Mustofa, Ubaedul; Asrori; Jayanto, Prabowo Yudo; Fauzi, Ahmad Syahrul; Runtiningsih, Sri (Universitas Muhammadiyah Surakarta, 2025)
Poverty in Indonesia is a serious problem, where the amount of meat consumption is decreasing, and the inequality of meat consumption between the rich and poor groups is increasing every year. The sacrificial worship has great potential to improve the community's economy, including livestock waqf, which can overcome the inequality of meat consumption. This study aims to analyze the initiation of social financing facilities through CWLQ to alleviate poverty in Indonesia. The research method used is panel data analysis by combining data from 34 provinces in Indonesia in the period 2019-2023. The independent variables used are sacrificial production, poverty in the previous period, economic growth, HDI, and the Gini coefficient, while the dependent variable is the poverty rate. The results of the analysis of sacrificial production, poverty in the previous period, economic growth, HDI, and the Gini coefficient will provide insight into the influence of economic and social factors in poverty alleviation efforts. This research is expected to contribute to developing more effective waqf-based policies in Indonesia, especially in supporting the national agenda to reduce poverty. These findings can also be a reference for policymakers and social and financial institutions designing sustainable CWLQ management strategies that positively impact the welfare of the wider community.